2018
DOI: 10.1007/s00167-018-4998-z
|View full text |Cite
|
Sign up to set email alerts
|

Over-voluming predicted by pre-operative planning in 24% of total knee arthroplasty

Abstract: IV, Retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Therefore, existing ready-made distal femoral prostheses can hardly cover the bone surface after cutting. Postoperative residual pain and rigidity are related to protrusion of the prosthesis and excessive size of the femoral components [ 5 ]. Implants not matching the bone surface after cutting may lead to ligament balance, patellar dislocation, and soft tissue impingement [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, existing ready-made distal femoral prostheses can hardly cover the bone surface after cutting. Postoperative residual pain and rigidity are related to protrusion of the prosthesis and excessive size of the femoral components [ 5 ]. Implants not matching the bone surface after cutting may lead to ligament balance, patellar dislocation, and soft tissue impingement [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that bone-implant mismatch can occur in TKA due to variation in the aspect ratio (ML/AP; ML = medial-lateral width, AP = anteroposterior length) and the asymmetry ratio (LAP/MAP; LAP = lateral anteroposterior, MAP = medial anteroposterior) [ 4 ]. Marmor et al reported that over-voluming occurred in 24% of TKA pre-operative planning [ 5 ]. In the past decade, studies on distal femur morphology have primarily focused on the aspect ratio of the distal femur [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive deformity correction may also lead to oversizing, particularly if under-resections are performed to maintain the joint line. 6,20 Furthermore, despite the production of genre- [21][22][23] or ethnic-specific implants, existing ranges fail to cover the polymorphism observed among populations. [24][25][26] Further development of existing ranges, or the advent of patient-specific implants, may be necessary before prosthetic oversizing or overhang can be completely eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite successful total knee arthroplasty (TKA), an estimated 20% of patients report dissatisfaction 1 due to unexplained pain and stiffness. [2][3][4] These complications were considered to result from an oversized or overhanging component, 5,6 which can lead to soft tissue impingement 7,8 or patellofemoral overstuffing. 9,10 Soft tissue balancing is an important step in successful TKA, enabling the surgeons to determine the optimal component size.…”
Section: Introductionmentioning
confidence: 99%
“… 83 The relationship between overstuffing and pain is unclear. A study by Marmor et al 84 showed that overstuffing TKRs is associated with extensive osteophytes and intra-articular femoral valgus which may suggest an association with excessive joint tension due to implant protrusion contributing to knee pain and stiffness. A study by Kemp et al 85 showed that there is no association between Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and combined patellofemoral overstuffing involving the patella and trochlea.…”
Section: Overstuffingmentioning
confidence: 99%